2009
DOI: 10.1002/lary.20758
|View full text |Cite
|
Sign up to set email alerts
|

Severe obstructive sleep apnea: Sleepy versus nonsleepy patients

Abstract: Severe OSA sleepy patients have a syndrome that is significantly more severe than nonsleepy patients. Sleepy patients have worse sleep-related breathing parameters, and their sleep patterns are lighter and more fragmented than nonsleepy patients. Apnea index appears as an important prognostic factor for excessive daytime sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
7
24
0
1
Order By: Relevance
“…In our study, the more severe of EDS, the higher of AHI, MiI, ODI and more sleep fragmentation. This phenomenon is similar to previous studies, OSAHS patients with the phenotype of EDS were younger and had a more severe symptoms 33, 34.Younger age and obesity were considered as significant risk factors for EDS in OSAHS patients 35.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the more severe of EDS, the higher of AHI, MiI, ODI and more sleep fragmentation. This phenomenon is similar to previous studies, OSAHS patients with the phenotype of EDS were younger and had a more severe symptoms 33, 34.Younger age and obesity were considered as significant risk factors for EDS in OSAHS patients 35.…”
Section: Discussionsupporting
confidence: 91%
“…However, as we do not have information on how long OSA has been present with each individual, these possible explanations are highly speculative and should be interpreted with caution. It is known that in patients with severe OSA, sleepy patients have a higher AHI and apnea index compared with nonsleepy patients [25]. In line with this, we found that the patients with AHT% > 45% were subjectively sleepier than the other patients despite the fact that all patients had severe OSA.…”
Section: Discussionsupporting
confidence: 89%
“…examination, particularly: Nasal endoscopy according to the modified criteria of endoscopic appearance as described by Lund et al, Mallampati Score, Tonsillar size grading according to the Brodsky Grading Scale; daytime sleepiness evaluation by means of the E.S.S. ; X‐ray cephalometry; Polysomnographic study (PSg) according to the guidelines of the Associazione Italiana Medicina del Sonno‐Associazione Italiana Pneumologi Ospedalieri (AimS‐AiPo) …”
Section: Methodsmentioning
confidence: 99%